Electric generator based on triboelectric effects - Tang, Timothy Yi Sheng (Nanyang Technological University, 2020)
There are various ways in which a generator can convert mechanical energy to electrical energy. The triboelectric mechanisms have many advantages over electromagnetic, piezoelectric and electrostatic mechanism. Over the years, triboelectric generators have become a sought- after solution for mechanical energy harvesting. Methods are found to be able to generate alternating current. However, direct current is more favourable as it does not require any rectification. This project aims to construct an electric generator or sensor by using a pair of materials with different electron affinities. A DC current can be generated when they are sliding against one another without changing the size of the contacting surface area. The experiments will be conducted to see the effects on the current generation when different solutions are added in between the two contacted surfaces. From the experimental results, we found out that when different solutions are added in between the contacted surfaces, the magnitude of the current is increased by one order of magnitude. Moreover, there is a presence of a non-zero current which is caused by double-layer capacitance. This study provides an in-depth understanding of electron transport at the contacted surfaces.